Estimating VS30 at South Korean Seismic Observatory Stations Through Horizontal and Vertical Ground Motions - Eric Yee; Chang-kyu Lee (Applied Sciences)
This investigation attempts to estimate time-averaged shear wave velocity in the upper 30 m of surficial material, VS30, from the horizontal-to-vertical spectral ratios, HVSRs, of seismic observatory stations in the South Korean region. From 2016 to 2023, a collection of 783 three-component ground motions were obtained from 19 stations operated by the Korea Institute of Geoscience and Mineral Resources. HVSRs were extracted from 5% damped acceleration and velocity RotD50 response spectra at each site. Peak HVSR frequencies and amplitudes were extracted and regressed to field-measured VS30s at available sites. An evaluation of different frequency and amplitude conditions was made to ascertain any effects on the regression. Findings included confirmation on minimum frequency and having amplitude conditions were unnecessary. Additionally, another peak frequency to VS30 relationship derived from Central and Eastern North America captured most of the behavior found in the Korean dataset.